Transforming the Hispanic Leader. Issue 4 (2nd October 2021) - Garza, Lisa; Pacheco, George; Gallardo, Juan; Castillo, Yvette; Henderson, Eddie
ABSTRACT: This essay describes the curriculum and implementation of the Hispanic Leadership Academy (HLA), designed to guide and mentor first generation, Hispanic students into becoming leaders in their community. The curriculum empowered students and encouraged them to take their developing leadership skills to the university. The authors believed that participation would assist in students' college success. Eleven undergraduate students from the University's College of Education and Social Sciences participated in a two-week intensive leadership academy in San Miguel de Allende, Mexico. While in Mexico, students learned leadership skills, found their voice, and were able to gain an understanding of how culture defines them.